2009
DOI: 10.1213/ane.0b013e3181b20c52
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of High Volume/Low Concentration and Low Volume/High Concentration Ropivacaine in Caudal Analgesia for Pediatric Orchiopexy

Abstract: We confirmed (with fluoroscopy) that a caudal block with 1 mL/kg ropivacaine spreads to T11 and to T6 with 1.5 mL/kg. If the total dose is fixed, caudal analgesia with a larger volume of diluted ropivacaine (0.15%) provides better quality and longer duration after discharge than a smaller volume of more concentrated ropivacaine (0.225%) in children undergoing day-case orchiopexy. The spread level of ropivacaine correlated significantly with the first oral acetaminophen time after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 18 publications
(16 reference statements)
6
38
1
5
Order By: Relevance
“…Additionally, caudal DEX with a low-concentration of local anesthetics induces less adverse effects (motor weakness, delayed micturition of urinary retention) that may affect early discharge from hospital, compared with a higher concentration of local anesthetics. 3,4,10,12,13,23) DEX has anxiolytic, sedative, and hypnotic properties caused by stimulation of the α2-adrenoceptor in the locus coeruleus in brain where it decreases a neuronal activation 9,24) and can reduce the requirement of concomitantly administered hypnotics, analgesics, or anesthetics. 25) Intravenous DEX significantly decreases the sevoflurane requirement 5,26) for anesthesia and EA during recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, caudal DEX with a low-concentration of local anesthetics induces less adverse effects (motor weakness, delayed micturition of urinary retention) that may affect early discharge from hospital, compared with a higher concentration of local anesthetics. 3,4,10,12,13,23) DEX has anxiolytic, sedative, and hypnotic properties caused by stimulation of the α2-adrenoceptor in the locus coeruleus in brain where it decreases a neuronal activation 9,24) and can reduce the requirement of concomitantly administered hypnotics, analgesics, or anesthetics. 25) Intravenous DEX significantly decreases the sevoflurane requirement 5,26) for anesthesia and EA during recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, high-volume/low-concentration (HVLC) regimens for caudal blocks in children (1.5 mL/kg of 0.1-0.2% local anesthetics) have gained popularity following a report by Silvani et al that demonstrated that a HVLC regimen provides a longer analgesic duration with less adverse effects than conventional dose/concentration. [3][4][5][6][7][8] However, the analgesic duration is still limited in caudal block with single-injection.Dexmedetomidine (DEX) is a highly selective α 2 adrenoceptor agonist with an α2/α1 selectivity ratio of 1600 : 1, and is eight times more potent than clonidine. 9) DEX is successfully used as an adjuvant in caudal blocks for children in order to reduce pain without inducing any significant respiratory and hemodynamic effects.…”
mentioning
confidence: 99%
“…We recently demonstrated that caudal analgesia with a larger volume (1.5 ml kg 21 ) of diluted ropivacaine 0.15% provides a longer duration than a smaller volume (1 ml kg 21 ) of more concentrated ropivacaine 0.225% in children undergoing day-case orchiopexy (554 vs 363 min), where the total dose of ropivacaine was fixed. 17 In both groups, however, the numbers of patients who required rescue oral acetaminophen after discharge were high (50% and 76%, respectively). In the present study, we demonstrated …”
Section: Discussionmentioning
confidence: 95%
“…This scale has been validated to score patients' satisfaction with anaesthetic technique and postoperative pain relief. 16 Sample size calculation was based on our previous data, 17 in which we found that mean (SD) to first analgesia in children who received caudal analgesia for orchiopexy using 1.5 ml kg 21 ropivacaine 0.15% was 554.5 (114.6) min after surgery. We calculated that 36 patients in each group would be required to show a 20% difference in this time (a¼0.05, b¼0.1).…”
Section: Methodsmentioning
confidence: 99%
“…The extent of analgesia following caudal block is dependent on the anatomic spread of solution within the epidural space; which in turn depends on the volume injected. 2,3 When the total drug dose is fixed, it is uncertain whether the volume or concentration of local anaesthetic influences the spread and quality of caudal analgesia. 4,5 In children, there is limited data regarding the relative effects of volume and concentration of local anaesthetic solutions used for caudal analgesia and the conclusions are still under debate.…”
Section: Introductionmentioning
confidence: 99%